Interaksi Kecepatan Terhadap Keterampilan Dribbling pada Permainan Futsal di Labu FC Kota Bengkulu - Saputra, Domi (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
An important component that must be mastered by a futsal player, among others, is a discipline that is built with high awareness to create a good lifestyle and excellent physical condition, because this sport requires a lot of movements such as forward, backward, and defending, so special techniques must be possessed. one of them is dribbling skills that require physical skills that allow the individual to quickly and efficiently change direction, accelerate, and slowdown in an attempt to react appropriately. If a futsal player has good speed when dribbling the ball, then the futsal player can free himself from the opponent's control and the ball is not easily captured by the opponent. Objective: To determine the relationship between speed and dribbling skills in futsal players. This research method is a type of analytic observational research with a cross-sectional approach. The sampling technique used a total sampling of 22 respondents. Data analysis uses the Pearson product-moment. the results showed that there was a significant relationship between speed and dribbling skills of futsal athletes, with a value of rx.y = 0.95> r (0.05) (22) = 0.423.